Formation of Russian farming: Problems and prospects - Andrey Inshakov, Vladimir Egorov, Evgeniya Shavina,; Omelchenko, Nikolay (Opción, 2019)
The article analyzes the state and prospects of development of family farms in the Russian agrarian sector via statistical analysis. The static data provided by the authors highlight the systemic deformation in shaping the structure of domestic agriculture. The conducted scientific research shows that the use of non-market methods of artificial planting of large forms of organization of agriculture is counterproductive. In conclusion, the formation of the modern farming segment of the Russian agrarian sector is complicated by both the factors arising from the historical and cultural context and the conditions generated by the post-Soviet economic reality